2020
DOI: 10.1016/j.eururo.2019.09.035
|View full text |Cite|
|
Sign up to set email alerts
|

EAU-ESMO Consensus Statements on the Management of Advanced and Variant Bladder Cancer—An International Collaborative Multistakeholder Effort†

Abstract: Background: Although guidelines exist for advanced and variant bladder cancer management, evidence is limited/conflicting in some areas and the optimal approach remains controversial. Objective: To bring together a large multidisciplinary group of experts to develop consensus statements on controversial topics in bladder cancer management. Design: A steering committee compiled proposed statements regarding advanced and variant bladder cancer management which were assessed by 113 experts in a Delphi survey. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 154 publications
(80 citation statements)
references
References 71 publications
1
70
0
6
Order By: Relevance
“…However, due to its significant cost for healthcare systems (34), prospective studies with high evidence level are still needed before its use can be formally adopted into consensus guidelines and recommendations (3,18,35,36). In support of its role in distant staging, a recent consensus statement revealed that 18F-FDG PET/CT is the imaging modality of choice to avoid overtreatment in oligometastatic patients with an agreement of 88% of participants (37) (Figure 1B).…”
Section: Distant Metastatic Stagingmentioning
confidence: 99%
“…However, due to its significant cost for healthcare systems (34), prospective studies with high evidence level are still needed before its use can be formally adopted into consensus guidelines and recommendations (3,18,35,36). In support of its role in distant staging, a recent consensus statement revealed that 18F-FDG PET/CT is the imaging modality of choice to avoid overtreatment in oligometastatic patients with an agreement of 88% of participants (37) (Figure 1B).…”
Section: Distant Metastatic Stagingmentioning
confidence: 99%
“…In its absence, retrospective nonrandomised trials have shown radical radiotherapy to offer very similar cancer-specific outcomes to cystectomy despite older radiation techniques and minimal use of concurrent chemotherapy [17e19]. Chemo-radiotherapy has also demonstrated comparable outcomes [20] and even improved overall survival [21] to surgery more recently, and is accepted as valid alternative by the joint EAU-ESMO consensus panel [22] and NICE [10]. In the current pandemic, bladder preservation therapy offers a sound choice for patients.…”
Section: Radical Cystectomymentioning
confidence: 99%
“…This treatment strategy was primarily used for the elderly, frail patients who were ineligible for RC [5][6][7]. Nowadays, multiple guidelines support the use of BST in the form of a trimodal therapy (TMT) as an alternative to primary RC with curative intent for selected, well-informed and compliant patients, who desire to retain their bladder [4,[8][9][10]. Despite the failure of all randomized controlled trials due to accrual (e.g.…”
Section: Introductionmentioning
confidence: 99%